2005
DOI: 10.1086/432564
|View full text |Cite
|
Sign up to set email alerts
|

Weapon Performance, Not Size, Determines Mating Success and Potential Reproductive Output in the Collared Lizard (Crotaphytus collaris)

Abstract: In territorial polygynous taxa, reproductive success reflects phenotypic variation. Using Crotaphytus collaris, a sexually dimorphic lizard in which males use the head (i.e., jaws and associated musculature) as a weapon when territorial interactions escalate to fights, we tested the hypothesis that weapon performance (i.e., bite force) is a better predictor of fitness than body or weapon size. Bite-force performance predicted the number of female home ranges overlapped, estimated mating success, and potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
162
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(168 citation statements)
references
References 58 publications
3
162
0
Order By: Relevance
“…Gaping displays of adult male collared lizards (Crotaphytus collaris) were found to provide an honest and accurate index of biting performance by exposing the major jaw-adductor muscle complex to rivals . Furthermore, biting force of male collared lizards predicted their access to females and their success in mating (Lappin and Husak 2005). These studies provide some of the best empirical evidence that displays of weapons honestly signal potential fighting performance.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Gaping displays of adult male collared lizards (Crotaphytus collaris) were found to provide an honest and accurate index of biting performance by exposing the major jaw-adductor muscle complex to rivals . Furthermore, biting force of male collared lizards predicted their access to females and their success in mating (Lappin and Husak 2005). These studies provide some of the best empirical evidence that displays of weapons honestly signal potential fighting performance.…”
mentioning
confidence: 79%
“…Signals that display the potential performance of weaponry could constitute an important component of many aggressive displays and reduce the occurrence of costly physical interactions. Indeed, substantial evidence indicates that animals use such specialized structures during aggressive encounters with conspecifics (e.g., Clutton-Brock 1982;Carrier et al 2002), and these structures help to determine dominance (Brown and Bartalon 1986;Lappin and Husak 2005).…”
mentioning
confidence: 99%
“…This sort of experiments is relevant because it is also possible that the evolutionary processes shaping male morphology in T. torquatus have been influenced also by intrasexual competition (Hews 1990, Ord et al 2001. Larger males may outstand in fighting ability (Hews 1990) because reptile combat success often correlates positively with body size (Cooper and Vitt 1987, Olsson 1992, Rodda 1992, Zucker and Murray 1996, Schuett 1997, Kratochvíl and Frynta 2002; but see Lappin and Husak 2005). Interestingly, Lappin and Husak (2005) observed that in males of Crotaphytus collaris the mating success seems associated with bite forces, which is probably related to fighting ability.…”
Section: Discussionmentioning
confidence: 99%
“…Larger males may outstand in fighting ability (Hews 1990) because reptile combat success often correlates positively with body size (Cooper and Vitt 1987, Olsson 1992, Rodda 1992, Zucker and Murray 1996, Schuett 1997, Kratochvíl and Frynta 2002; but see Lappin and Husak 2005). Interestingly, Lappin and Husak (2005) observed that in males of Crotaphytus collaris the mating success seems associated with bite forces, which is probably related to fighting ability. A following step from our study would be measuring bite forces and fighting ability in dominant males of Tropidurus torquatus, in order to verify if morphological differences and reproductive success are also related to combat efficiency and the capacity to retain the best territories in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation